DAMPAK LITERASI KEUANGAN SYARIAH DAN KEPERCAYAAN TERHADAP KEPUTUSAN MENABUNG DI BANK MUAMALAT KCP STABAT - Nurul Nurul; Dinda Syalshabila; Zulham Efendi Nasution; Khairani Khairani; Muhammad Saleh (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to analyze the influence of Islamic financial literacy and trust on savings decisions at Bank Muamalat KCP Stabat. The method used is quantitative research with data collection techniques through the distribution of questionnaires to 78 respondents who are active customers for at least 6 months. The collected data were tested for validity, reliability, normality, multicollinearity, and heteroscedasticity, then analyzed using multiple linear regression with the assistance of statistical software. The results of the study indicate that Islamic financial literacy has a significant positive effect on savings decisions, meaning that the better customers' understanding of Islamic financial principles and products, the higher their tendency to choose Islamic savings. Trust also has a significant positive influence on savings decisions, indicating that customers' confidence in the bank's security, transparency, and compliance with Islamic principles is an important factor in determining their choice. Together, these two variables explain 50.1% of the variation in savings decisions, while the remaining variation is influenced by other factors such as income, education level, and service convenience. These findings have practical implications for Bank Muamalat KCP Stabat to enhance its Islamic financial literacy education programs through outreach, easily understandable information media, and improved service quality to strengthen customer trust. This study is limited to one branch and uses a survey method, so further research is recommended to expand the sample, add related variables, and use a mixed-method approach for more comprehensive results. Keywords: Islamic Financial Literacy, Trust, Savings Decisions